Outcome of fixation of acromioclavicular joint dislocation type-iii with clavicular hook plate - Thapa, Pabin; Sapkota, Krishna; Ranjeet, Niraj; Onta, Pratyenta Raj; Wahegaonkar, Krishna; Thapa, Upendra Jung (Nepal Journal of Medical Sciences, 2020)
Introduction: Acromioclavicular (AC) joint dislocation is one of the most common shoulder injuries accounting for approximately 9-12% of all shoulder girdle injuries. Rockwood classification of AC joint dislocation is the most widely accepted classification system which classifies the injury into six types. Surgical management with open reduction and fixation with clavicular hook plate without the repair of coracoclavicular ligament has proved to be one of the best treatment options for Type III AC joint dislocations. Methods: Twenty-three patients with Rockwood Type III AC joint dislocation were included in the study. Open reduction was done and the fixation was done with the clavicular hook plate. The functional outcomes were assessed before and two months after the implant was removed using the Constant- Murley Score. Results: A total of 23 patients were included in the study with the mean age of 30.74 years. The plates were removed on an average of 6.43 months and mean follow up was 8.83 months. The functional outcome was assessed using the Constant- Murley Shoulder score. The pain scores were significantly better after the implant removal was done (p= 0.007). The final mean constant score was 74.6 ± 4.11 before removal and 93.91 ± 2.71 after implant removal and all the 23 patient had excellent result (>90 points). Conclusions: The pre-contoured clavicular hook plate has proved to be a good implant option in the fixation of Rockwood Type III AC joint dislocation without the need of any ligamentous repair